Factors influencing students’ satisfaction in using wireless internet in higher education - Islam, Abu Yousuf Mohammed Atiquil; Mok, Magdalena Mo Ching; Xiuxiu, Qian; Chin, Hai Leng (Emerald, 2018)
Purpose – In this age of exponential knowledge growth, where wireless internet is playing a dominant role, the concerned authorities of higher education have to ensure that this tool remains within the reach of the students. However, there has been as yet little research indicating its success in China. This paper aims to examine factors that influence students’ satisfaction (SAT) in using wireless internet in higher education for the purpose of learning. The second aim of this study is to identify if gender has a moderating effect on students’ SAT in using wireless internet in higher education. Design/methodology/approach – Data from a total of 283 students from five colleges of a comprehensive public university in China (Foreign Language Studies, Business, Education, Biology and Chemistry, and Mathematics and Engineering) were collected for this study. The reliability and validity of the measurement scale were established through a Rasch model using Winsteps version 3.94. The technology satisfaction model (TSM) was validated applying structural equation modelling (SEM) using AMOS to test the causal relationships among the constructs. Findings – The results of this study revealed that students’ SAT was directly influenced by perceived usefulness (PU) and ease of use of wireless internet. Besides, students’ perceived ease of use (PEU) and usefulness were directly affected by their computer self-efficacy. On the other hand, students’ computer selfefficacy had an indirect effect on their SAT mediated by ease of use and perceived usefulness, respectively. The findings also discovered that gender did exert effect as a moderating variable towards students’ SAT in using wireless internet in higher education. Practical implications – The TSM was shown to be a useful model to measure students’ SAT in using wireless internet in a different culture.